IMPACT OF SHOULDER ROTATOR CUFF DISORDER ON HUMAN POSTURE (Physical Culture and Sport: Scientific Perspective, 2024)
Medical research has found that shoulder rotator cuff disorders are a common problem, often resulting from trauma, overuse, or degenerative changes. The results showed that this condition can significantly affect a person's posture and the way they move. The study also found a link between rotator cuff damage and a person's posture, specifically, participants with abnormal posture were more likely to have rotator cuff muscle tears. Considering these results, it is important to understand the relationship between the state of the shoulder joint and posture for the effective diagnosis and treatment of diseases of this area.This article systematically analyzes the impact of shoulder rotator cuff damage on various aspects of human physiology and functioning during walking. It has been found that rotator cuff damage can significantly limit motor activity in the shoulder joint, which in turn affects the way a person performs arm and upper body movements while walking. In addition, feeling pain or discomfort in the shoulder can lead to changes in the mechanics of movement and walking, as the person tries to avoid the discomfort, which can lead to uneven stress on the muscles and joints during walking.Additionally, a rotator cuff injury can also affect a person's posture when walking, causing them to lean forward or change their posture to reduce stress on the injured shoulder area. These changes in posture can affect overall walking mechanics and can also lead to loss of shoulder stability and changes in body balance. This impact of rotator cuff disorders highlights the importance of understanding this aspect for the effective diagnosis and treatment of shoulder joint diseases and the maintenance of optimal human functionality during walking.The study describes the effect of different body positions on the kinematics of the scapula muscles during external rotation of the shoulder. The results showed that changes in the position of the trunk significantly affect the angle of inclination of the scapula and the external rotation of the shoulder. In the flexion-extension position of the trunk, there was a decrease in the external rotation of the shoulder, but an increase in the activity of the scapula muscles. These results emphasize the importance of correct trunk position for optimal functioning of the scapular muscles and shoulder mechanics. In addition to this, another study showed an important effect of body position during sitting on pain provocation and pain level during clinical shoulder tests in patients with shoulder problems.
Keywords: changes in a person's posture; activity of the muscles of the shoulder rotator cuff; types of posture; body position; shoulder rotation